Sanitation Conditions to Fly Density In Duck Livestock in Gebang Village, Pakel District, Tulungagung - Ayuni, Via Dwi; Setyo Budi Susanto (Indonesian Journal of Nutritional Epidemiology and Reproductive, 2021)
Livestock pen sanitation is sanitation which includes the success of the pen and the environment, because with the condition of the pen and the clean environment, the health of both livestock and their owners will be guaranteed.. The purpose of this study was to analyze the influence sanitary conditions of fly density in duck livestock in Gebang Village, Pakel District, Tulungagung Regency. The design of this research is an observational quantitative study with a cross sectional approach with the focus of the research being directed to analyze the effectsanitary conditions of fly density in duck livestock in Gebang Village, Pakel District, Tulungagung Regencywith a population of 40 respondents and a sample of 36 respondents who were taken using the simple random sampling technique. The findings show that hNearly half of the respondents have a sanitary condition with a sufficient category of 15 respondents (41.7%). Most of the respondents have a high fly density category of 29 respondents (80.7%). The results of the study used the test Linear Regression indicates that the p-value is 0.000 <0.05, then H1 is accepted, so it is concluded that there is the effect of sanitation conditions on the density of flies in duck livestock in Gebang Village, Pakel District, Tulungagung Regency. Business owners are advised to further improve duck coop sanitation in terms of providing disinfection, use of PPE, prevention of other animals, cleaning of cages, waste management.